Trends in Surgical Morbidity and Survival Outcomes for Radical Hysterectomy in West China: An 11-Year Retrospective Cohort Study - Jing, Huining; Yang, Ying; Liu, Yinxia; Zou, Peijun; Li, Zhengyu (Frontiers in Oncology, 2022)
Objectives To vertically analysis the trend of surgical approaches, demographics, surgical morbidity and long-term survival outcomes of early-stage cervical cancer over the past 11 years and determine whether there have been any significant changes. Methods A total of 851 patients with cervical cancer diagnosed between January 2008 and June 2018 at single-center in China were included in this retrospective study. Trends in rate of MIS, demographics, surgical morbidities, and long-term survival outcomes were determined. The demographics, pathologic factors, surgical morbidity, and survival outcomes were compared when stratified by the year of operation. Results There was a significant increase in rate of LRH performed over the study period, from 7.8% in 2008 to 72.5% in 2018 (p< 0.0001). Those who underwent ARH in the second half of study period (2014-2018) were significantly older (45.01 v. 47.50 years; p= 0.001). The most impressive changes over the past 11 years have occurred in the surgical morbidity in both ARH and LRH groups. The median blood loss of ARH group was decreased（400ml v. 500ml, p <0.0001) when compared to the first few years of the study period, which in LRH group was (150ml v. 350ml, p <0.0001) respectively. Similarly, allogeneic blood transfusions and hospital stay have all decreased dramatically over time in both approaches. Whereas, our study did not reveal any significant statistical changes of long-term survival outcomes over the follow-up period in either group. Conclusions Our study demonstrates that great progress in surgically managed cervical cancer have been made over the last decade in West China. The year of operation does not appear to influence the long-term survival but the surgical morbidity impressively decreased over the study period in two approaches.